Genetic control and early selection of three Corymbia species - Miranda, Leticia; Estopa, Regiane Abjaud; Paludeto, João Gabriel Zanon; Tambarussi, Evandro Vagner [UNESP] (Canadian Science Publishing, 2024)
The main objective of this study was to investigate genetic control for individual volume and genetic and phenotypic correlation between trait measured at two different ages. We also assessed three different selection intensities (i = 1%, i = 5% and i = 10%) to understand the effects on genetic gain and effective size. Eight progeny tests were evaluated which included three tests of Corymbia citriodora subsp. citriodora) (CCT), two tests of C. citriodora subsp. variegata (CCV), and three tests of C. torelliana (CTO). Narrow-sense heritability (Fromula Presented) ranged from 0.26 to 0.62 for the CCT tests, from 0.07 to 0.21 for the CCV tests, and from 0.14 to 0.69 for CTO. The coefficients of individual genetic variation (Fromula Presented) ranged from 22.5% to 63.9% for CCT, from 19.3% to 28.3% for CCV, and from 22.8% to 41.3% for CTO. Considering a selection intensity of 10%, the Ne after selection would range from 31 to 98 for CCT, 36 to 47 for CCV, and 45 to 62 for CTO. For the TP8 CTO test, a selection intensity greater than 10% is recommended. With a selection intensity of 10%, genetic gains ranged from 25 to 107% for CCT, from 14 to 27% for CCV, and from 19 to 64% for CTO.
Keywords: age of selection; growth; progeny tests; quantitative genetics; volume